Methodology Followed in the Determination of the Peak Hour Parameters for Buenos Aires City Airport - Pesarini, Alejandro J. (2010)
The estimated demand used in the planning process of Buenos Aires City Airport Master Plan, developed by the Unit of Renegotiation and Contract Analysis of Public Services from Argentina, has not included infrastructure planning parameters: passenger peak hour and operation peak hour. These parameters must be determined to properly project, for the short, medium and long term development stages, the airport air-side, land-side and support elements. In order to consider infrastructure planning parameters two different methods have been used, all based in the historical data of year 2007: the peak hour movements and the airplane distribution, determined from the six peak hours; and the peak hour passenger distribution, determined from a FAA index. Also the traffic month distribution and the peak hour transit for national and international passengers for arrivals and departures have been determined. The results and conclusions of these determinations are presented.